Tomato Reproductive Success Is Equally Affected by Herbivores That Induce or That Suppress Defenses - Liu, Jie; Legarrea, Saioa; Kant, Merijn R. (Frontiers in Plant Science, 2017)
Herbivory induces plant defenses. These responses are often costly, yet enable plants under attack to reach a higher fitness than they would have reached without these defenses. Spider mites (Tetranychus ssp.) are polyphagous plant-pests. While most strains of the species T. urticae induce defenses at the expense of their performance, the species T. evansi suppresses plant defenses and thereby maintains a high performance. Most data indicate that suppression is a mite-adaptive trait. Suppression is characterized by a massive down-regulation of plant gene-expression compared to plants infested with defense-inducing mites as well as compared to control plants, albeit to a lesser extent. Therefore we hypothesized that suppression may also benefit a plant since the resources saved during down-regulation could be used to increase reproduction. To test this hypothesis, we compared fruit and viable seed production of uninfested tomato plants with that of plants infested with defense-inducing or defense-suppressing mites. Mite-infested plants produced fruits faster than control plants albeit in lower total amounts. The T. evansi-infested plants produced the lowest number of fruits. However, the number of viable seeds was equal across treatments at the end of the experiment. Nonetheless, at this stage control plants were still alive and productive and therefore reach a higher lifetime fitness than mite-infested plants. Our results indicate that plants have plastic control over reproduction and can speed up fruit- and seed production when conditions are unfavorable. Moreover, we showed that although suppressed plants are less productive in terms of fruit production than induced plants, their lifetime fitness was equal under laboratory conditions. However, under natural conditions the fitness of plants such as tomato will also depend on the efficiency of seed dispersal by animals. Hence we argue that the fitness of induced plants in the field may be promoted more by their higher fruit production relative to that of their suppressed counterparts.